CTXφ: Exploring new alternatives in host factor-mediated filamentous phage replications. Issue 2 (2nd April 2016) - Martínez, Eriel; Campos-Gómez, Javier; Barre, François-Xavier
ABSTRACT: For a long time Ff phages from Escherichia coli provided the majority of the knowledge about the rolling circle replication mechanism of filamentous phages. Host factors involved in coliphages replication have been fully identified. Based on these studies, the function of Rep protein as the accessory helicase directly implicated in filamentous phage replication was considered a paradigm. We recently reported that the replication of some filamentous phages from Vibrio cholerae, including the cholera toxin phage CTXφ, depended on the accessory helicase UvrD instead of Rep. We also identified HU protein as one of the host factors involved in CTXφ and VGJφ replication. The requirement of UvrD and HU for rolling circle replication was previously reported in some family of plasmids but had no precedent in filamentous phages. Here, we enrich the discussion of our results and present new preliminary data highlighting remarkable divergence in the lifestyle of filamentous phages.